Search for boosted low-mass resonances decaying into hadrons produced in association with a photon in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; E. Aakvaag; B. Abbott; S. Abdelhameed; K. Abeling; N. J. Abicht; S. H. Abidi; M. Aboelela; A. Aboulhorma; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics)
Abstract Many extensions of the Standard Model, including those with dark matter particles, propose new mediator particles that decay into hadrons. This paper presents a search for such low mass narrow resonances decaying into hadrons using 140 fb −1 of proton-proton collision data recorded with the ATLAS detector at a centre-of-mass energy of 13 TeV. The resonances are searched for in the invariant mass spectrum of large-radius jets with two-pronged substructure that are recoiling against an energetic photon from initial state radiation, which is used as a trigger to circumvent limitations on the maximum data recording rate. This technique enables the search for boosted hadronically decaying resonances in the mass range 20–100 GeV hitherto unprobed by the ATLAS Collaboration. The observed data are found to agree with Standard Model predictions and 95% confidence level upper limits are set on the coupling of a hypothetical new spin-1 Z′ resonance with Standard Model quarks as a function of the assumed Z′-boson mass in the range between 20 and 200 GeV.